Long‐term follow up of serum pepsinogens in patients with gastric cancer or dysplasia after Helicobacter pylori eradication. Issue 9 (10th March 2020) - Noh, Gitark; Kim, Nayoung; Choi, Yonghoon; Lee, Hye Seung; Hwang, Young Jae; Kim, Hee Jin; Yoon, Hyuk; Shin, Cheol Min; Park, Young Soo; Lee, Dong Ho
Abstract: Background and Aim: Few studies have evaluated the change in serum pepsinogen (sPG) levels after the eradication of Helicobacter pylori . The aim of this study was to evaluate the effect of H. pylori eradication on sPG levels in patients with gastric cancer/dysplasia in comparison to a control group. Methods: We prospectively enrolled 368 patients with gastric cancer/dysplasia and 610 control subjects. H. pylori status and sPG levels were measured before and after eradication. The follow‐up time points were classified as < 12, 12–23, 24–35, and ≥ 36 months. Results: In 179 H. pylori ‐eradicated patients with gastric cancer/dysplasia and 168 control group subjects, sPG I significantly decreased, and the sPG I/II ratio significantly increased after eradication compared to baseline, and this improvement in sPG values was maintained during all follow‐up time points. Significant differences in sPG I and the sPG I/II ratio were observed between the gastric cancer/dysplasia group and the control group < 24 months after eradication. However, these differences in sPG values disappeared after ≥ 24 months of follow up. Moreover, significant differences in the intestinal metaplasia grade were observed between these two groups before eradication until < 24 months after eradication. However, these differences in the intestinal metaplasia grade disappeared after ≥ 24 months of follow up in the corpus. Conclusion: The sPG values and intestinal metaplasia grade (corpus) in the gastric cancer/dysplasia group became similar to those in the control group at long‐term follow up after H. pylori eradication. It might be related with the reduction of metachronous gastric neoplasm.